LEVEL OF COMPETENCY OF GRADUATES OF THE SPECIAL SCIENCE CAMPUS TEACHER EDUCATION INSTITUTE - Faridah Yakob; Lee Leh Hong (Journal Civics And Social Studies, 2022)
The Malaysian Teacher Standard is a standard that outlines the professional competencies that teachers should achieve, and the requirements that should be provided by agencies and tertiary training institutions to help teachers achieve the specified level of competency. This study was carried out to review the competency level of the 2018 Bawan students who had just completed their five (5) years of study at the IPG Ilmu Khas Campus, Kuala Lumpur. The study sample consisted of 85 students who had attended studies in the specialization areas of Special Education (Learning Problems, Vision Problems, Hearing Problems), Music Education, Physical Education and Health. This study uses a quantitative approach using the SGM 2.0 Personal Competency Checklist (SSKD). The Competency Dimensions in the SGM 2.0 Framework are the main reference in this study. The results of the study show that the overall competency level for the SGM 2.0 domain of PISMP students taking June 2018 IPGKIK is at min=3.0 (SP=0.78). This shows that students have succeeded in achieving the SGM 2.0 competency standards in the four SGM 2.0 domains, namely science orientation, science orientation, instructional, community involvement and personal quality. Even though the min for all four domains reached the SGM competency standard of 2.0, it was found that the min for the science orientation domain was 2.95 and the min for the instructional domain was 2.98 compared to the community engagement domain which was min 3.00 and the personal quality domain with min 3.08. The reviewer also suggests that IPGM continues to design and improve the programs it offers taking into account current challenges in order to raise a generation of students who can face and handle new challenges, especially in the era of the 21st century information revolution in order to produce teachers who are competent and have an educational spirit and complies with SGM 2.0 standards.